Conducting in-depth interviews with and without voice recorders: a comparative analysis. (October 2020) - Rutakumwa, Rwamahe; Mugisha, Joseph Okello; Bernays, Sarah; Kabunga, Elizabeth; Tumwekwase, Grace; Mbonye, Martin; Seeley, Janet
The use of audio recordings has become a taken-for-granted approach to generating transcripts of in-depth interviewing and group discussions. In this paper we begin by describing circumstances where the use of a recorder is not, or may not be, possible, before sharing our comparative analysis of audio-recorded transcriptions and interview scripts made from notes taken during the interview (by experienced, well-trained interviewers). Our comparison shows that the data quality between audio-recorded transcripts and interview scripts written directly after the interview were comparable in the detail captured. The structures of the transcript and script were usually different because in the interview scripts, topics and ideas were grouped, rather than being in the more scattered order of the conversation in the transcripts. We suggest that in some circumstances not recording is the best approach, not 'second best'.